Effect of processing parameters and pore structure of nanostructured silica aerogel on the physical properties of aerogel blankets. (16th May 2018) - Latifi, Fatemeh; Talebi, Zahra; Khalili, Haleh; Zarrebini, Mohammad
Abstract: This work investigates the influence of processing parameters and aerogel pore structure on the physical properties and hydrophobicity of aerogel blankets. Aerogel blankets were produced by in situ synthesis of nanostructured silica aerogel on a polyester nonwoven substrate. Nitrogen adsorption-desorption analysis, contact angle test and FE-SEM images were used to characterize both the aerogel particles and the blankets. The results showed that the weight and thickness of the blanket were reduced when the low amount of catalyst was used. A decrease in the aerogel pore size from 22 to 11 nm increased the weight and thickness of the blankets. The xerogel particles with high density and pore size of 5 nm reduced the blanket weight. Also, the blanket weight and thickness were increased due to increasing the sol volume. It was found that the hydrophobicity of aerogel blankets is not influenced by sol volume and pore structure of silica aerogel.